Computer Self-administered Screening for Substance Use in University Student Health Centers - McNeely, Jennifer (J Am Coll Health, 2018)
OBJECTIVE: To characterize the prevalence of tobacco, alcohol, and drug use and the acceptability of screening in university health centers. PARTICIPANTS: 502 consecutively recruited students presenting for primary care visits in February and August, 2015, in two health centers. METHODS: Participants completed anonymous substance use questionnaires in the waiting area, and had the option of sharing results with their medical provider. We examined screening rates, prevalence, and predictors of sharing results. RESULTS: Past-year use was 31.5% for tobacco, 67.1% for alcohol (>4 drinks/day), 38.6% for illicit drugs, and 9.2% for prescription drugs (non-medical use). A minority (43.8%) shared screening results. Sharing was lowest among those with moderate-high risk use of tobacco (OR=0.37, 95% CI 0.20–0.69), alcohol (OR=0.48, 95% CI 0.25–0.90), or illicit drugs (OR=0.38, 95% CI 0.20–0.73). CONCLUSIONS: Screening can be integrated into university health services, but students with active substance use may be uncomfortable discussing it with medical providers.